Analysis of the mechanical properties of conveyor belts on the three main stages of production. (May 2016) - Barburski, Marcin
Conveyors belts are used wherever it is necessary to transport materials quickly and promptly. They are made of fabric-rubber core (carcass) and rubber covers. The carcass may consist of several spacers made of synthetic polyamide–polyester fabrics impregnated with a solution of latex that provides an intermediate layer to prevent delamination of the vulcanized composite. The main goal of this research work is to analyse the mechanical properties of conveyor belts during three main stages of production: raw fabric, fabric impregnated with latex, and conveyor belt. For this purpose, nine fabrics of different weaves with a width of 1 m were produced with polyester warp and polyamide weft threads. The fabrics were coated with latex and then vulcanized. Subsequently, the structural parameters and the mechanical properties of each product were measured at each of the three stages of conveyor belt production. This article presents the effect of fabric structure on the mechanical properties of the products of these three production stages. Results show that differences in the mechanical properties of products at different stages of conveyor belt production depend on number of intersections of yarns in woven fabrics. In addition, significant differences were observed in the mechanical properties depending on the applied weaves.